2013
DOI: 10.1021/ic401280e
|View full text |Cite
|
Sign up to set email alerts
|

Marinite Li2M(SO4)2 (M = Co, Fe, Mn) and Li1Fe(SO4)2: Model Compounds for Super-Super-Exchange Magnetic Interactions

Abstract: New materials initially designed for battery electrodes are often of interest for magnetic study, because their chemical compositions include 3d transition metals. We report here on the magnetic properties of marinite phases Li2M(SO4)2 (M = Fe, Co, Mn) and Li1Fe(SO4)2, which all order antiferromagnetically at low temperature. From neutron powder diffraction, we propose a model for their ground-state magnetic structures. The magnetism of marinite Li2M(SO4)2 compounds unambiguously results from super-super-excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
66
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 41 publications
7
66
1
Order By: Relevance
“…Conversely, each SO 4 group is only bound to three MO 6 octahedra, with the fourth corner of the non-shared tetrahedron pointing to an open channel where lithium ions reside. Later, in 2013, Reynaud et al [102] reported that Li 2 Mn(SO 4 ) 2 crystallized into the same structure as the iron and cobalt compounds, which was confirmed by Rietveld refinement of the XRD data.…”
Section: Carbonophosphatesmentioning
confidence: 75%
See 4 more Smart Citations
“…Conversely, each SO 4 group is only bound to three MO 6 octahedra, with the fourth corner of the non-shared tetrahedron pointing to an open channel where lithium ions reside. Later, in 2013, Reynaud et al [102] reported that Li 2 Mn(SO 4 ) 2 crystallized into the same structure as the iron and cobalt compounds, which was confirmed by Rietveld refinement of the XRD data.…”
Section: Carbonophosphatesmentioning
confidence: 75%
“…First, stoichiometric amounts of Li 2 SO 4 and MSO 4 were thoroughly mixed using a Spex Miller 8000M, with the resulting powder next pressed into a pellet. Finally, the pellet is annealed at 325°C for 12-48 h, either under air (M = Co, Mn) or in a quartz tube sealed under vacuum (M = Fe) [102].…”
Section: Carbonophosphatesmentioning
confidence: 99%
See 3 more Smart Citations